2017
DOI: 10.1177/0886260517696857
|View full text |Cite
|
Sign up to set email alerts
|

Poor Relationships and Physical Violence at School Are Associated With More Forms of Psychological Violence Among Brazilian Teachers: A Cross-Sectional Study

Abstract: Our purpose was to identify individual and work-related factors that are associated with psychological violence (PV) and are related to a higher number of PV forms among teachers. This cross-sectional study included 789 elementary and high school teachers in a municipality in southern Brazil. Data were obtained through interviews and a self-administered questionnaire. PV was characterized by reports of insults from students, humiliation by colleagues or teachers, and threats in the 12 months preceding the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
0
14
0
7
Order By: Relevance
“…Pemahaman akan payung hukum penyelesaian tindak kekerasan di sekolah oleh para guru, wajib pula untuk dilaksanakan. 13…”
Section: A Pendahuluanunclassified
See 1 more Smart Citation
“…Pemahaman akan payung hukum penyelesaian tindak kekerasan di sekolah oleh para guru, wajib pula untuk dilaksanakan. 13…”
Section: A Pendahuluanunclassified
“…Kekerasan tersebut tidak hanya kekerasan secara fisik, namun juga kekerasan secara psikis berupa ancaman, intimidasi, olok-olok, penghinaan, yang menyebabkan rasa trauma pada korban. 13 Berdasarkan infografis dari Kementerian Pemberdayaan Perempuan dan Perlindungan Anak di atas, menunjukkan bahwa siswa laki-laki dan perempuan menyebutkan bahwa guru dan petugas sekolah sebagai pelaku kekerasan. Sebagian besar siswa mengalami pem-bully-an di sekolah.…”
Section: Kekerasan DI Lingkungan Sekolahunclassified
“…We chose to study the relationship between burnout and road traffic accidents among Brazilian teachers, as they are exposed to several job stressors, such as work overload, violence, insufficient resources and social devaluation of their profession (Assunção & Abreu, 2019;Melanda et al, 2020). According to a worldwide evaluation of the condi- shifts of the day, from early morning until around 11 p.m.; thus, many teachers extended their daily working hours to increase their income.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to study the relationship between burnout and road traffic accidents among Brazilian teachers, as they are exposed to several job stressors, such as work overload, violence, insufficient resources and social devaluation of their profession (Assunção & Abreu, 2019; Melanda et al, 2020). According to a worldwide evaluation of the conditions of teaching and learning (Organisation for Economic Co‐operation and Development, 2014), Brazilian teachers have, compared with teachers from other countries who participated in the research, a greater number of students per classroom and spend more hours per week in classrooms and in bureaucratic tasks or in work after regular working hours.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies involving this population have focused on health problems that could influence absenteeism, predominantly chronic mental health (15) and physical conditions (16) . Previous studies have shown that teachers' health is affected by work in different ways, leading to stress (17) , burnout syndrome (17,18) , exposure to school violence (19) , anxiety and depression (17) . In addition to affecting teachers' own health, these professionals are important role models for their students, and their knowledge, attitudes, and eating behaviours may be barriers to promoting healthy food habits for their students (20) .…”
mentioning
confidence: 99%